(untitled) (Global Journal of Science Frontier Research, 2020)
Preliminary laboratory studies have indicated that the pteromalid ecto-pupal parasitoid, Trichomalopsis uziae Sureshan & Narendra Kumar, has been reported to possess immense potential to serve as a biological control agent of the tachinid fly, Exorista bombycis (Louis), which inflicts a cocoon yield reduction of 10-20% in the southern states of India. The present laboratory investigations aims at generating information on the impact of age (0-10 days at 1 day apart in age) and size (big and small) of the parasitoid in addition to mating combinations (sib, conspecific, and random) on its reproductive performance when the pupae of E. bombycis were parasitized.